An epistemic illumination of the acceptance of advice in Chinese phone-in counseling for family problems. (June 2022) - Peng (彭卓), Zhuo
This study, by means of conversation analysis, comprehensively illuminates the advisee's acceptance of advice in Chinese phone-in counseling for family problems from the perspective of Epistemics, and reveals advisee's type of management of the epistemic status relationship as well as the epistemic stances during executing the management. The study finds that the advisee tacitly approved of the asymmetric relationship of epistemic status between an adviser and himself/herself when accepting advice; that this type of relationship management can be executed through four kinds of epistemic stances; that these stances actually reflect the advisee's positioning of asymmetric relationship of knowledge distribution of both parties. This study investigates the acceptance of advice from the perspective of Epistemics, which can extend the theoretical perspective of the researches on responses to advice and give new illumination of the advisory interaction.